Electrode composition, electrode, and battery
The electrode composition, featuring a polymer with a nitrogen-containing heterocyclic structure, addresses the resistance increase in lithium-ion batteries during high-temperature storage by suppressing electrolyte decomposition, thereby improving battery performance and safety.
Patent Information
- Application Number
- JP2023122890
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
Lithium-ion secondary batteries experience an increase in resistance after long-term storage at high temperatures, which is not effectively addressed by existing technologies.
The electrode composition includes a polymer with a nitrogen-containing heterocyclic structure containing an unsaturated bond, where the structural unit derived from such compounds constitutes more than 50 mol% of the polymer, combined with an active material and a binder, to form electrodes that suppress electrolyte decomposition and resistance increase.
The electrode composition effectively reduces the increase in battery resistance after high-temperature storage, enhancing the battery's performance and safety.
Smart Images

Figure 2025018838000002 
Figure 2025018838000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composition for an electrode, an electrode, and a battery. [Background technology]
[0002] Lithium-ion secondary batteries have been attracting attention as batteries with high energy density.
[0003] Patent Document 1 discloses a coating liquid used in the manufacture of battery electrodes. The coating liquid disclosed in Patent Document 1 contains a solvent, a binder, a carbon-based substance, and a polymer having a nitrogen-containing five-membered ring structure. The content of the polymer is 1 ppm or more and 10,000 ppm or less with respect to the total mass of the coating liquid. Patent Document 1 specifically discloses a copolymer of polyvinylpyrrolidone and polyvinylimidazole (monomer ratio 50:50) as the polymer. The coating liquid disclosed in Patent Document 1 is used as a raw material for an electrode material layer of a battery. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-63423 A Summary of the Invention [Problem to be solved by the invention]
[0005] For batteries, there is a demand for an electrode composition that can suppress an increase in resistance after long-term (e.g., 28 days) storage in a high-temperature environment (e.g., 60°C) (hereinafter also referred to as "resistance after high-temperature storage").
[0006] In view of the above circumstances, an object of the present disclosure is to provide an electrode composition, an electrode, and a battery that can suppress an increase in resistance after high-temperature storage of a battery. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects.
[0008] <1> Contains a polymer (A), the polymer (A) contains a structural unit (a) having a five- or six-membered nitrogen-containing heterocyclic structure, and the nitrogen-containing heterocyclic structure contains an unsaturated bond; A composition for an electrode, wherein the proportion of the structural unit (a) in the polymer (A) is more than 50 mol % relative to the total of all structural units constituting the polymer (A).
[0009] <2> The proportion of the structural unit (a) is 60 mol % or more. <1> The electrode composition according to claim 1 .
[0010] <3> The structural unit (a) includes a structural unit derived from vinylimidazole. <1> or <2> The electrode composition according to claim 1 .
[0011] <4> The above-mentioned further contains an active material (B) and a binder (C). <1> ~ <3> 13. The electrode composition according to claim 12,
[0012] <5> The active material (B) contains a carbon-based compound. <4> The electrode composition according to claim 1 .
[0013] <6> The content of the polymer (A) relative to the solid content of the composition for an electrode is 0.01% by mass to 1.0% by mass. <1> ~ <5> 13. The electrode composition according to claim 12,
[0014] <7> A current collector; The above <1> ~ <6> A solid material of the electrode composition according to any one of the above items, , an electrode.
[0015] <8> The above <7> A battery comprising the electrode according to claim 1.
[0016] According to the present disclosure, there are provided an electrode composition, an electrode, and a battery capable of suppressing an increase in resistance after high-temperature storage of a battery. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a laminated battery, which is an example of a battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0019] In this specification, the amount of each component in a composition means, when a plurality of substances corresponding to each component are present in the composition, the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0020] In this specification, "(meth)acrylate" refers to acrylate or methacrylate. (1) Electrode composition The electrode composition of the present disclosure (hereinafter also simply referred to as "electrode composition") contains a polymer (A). The polymer (A) contains a structural unit (a). The structural unit (a) has a five- or six-membered nitrogen-containing heterocyclic structure, and is derived from a compound (hereinafter also referred to as "monomer (a)") in which the nitrogen-containing heterocyclic structure contains an unsaturated bond. The proportion of the structural unit (a) in the polymer (A) relative to the total of all structural units constituting the polymer (A) (hereinafter also simply referred to as "proportion of structural unit (a)") is more than 50 mol%.
[0021] The term "unsaturated bond" refers to a double bond or a triple bond.
[0022] The term "heterocyclic structure" refers to a ring structure composed of carbon atoms and heteroatoms (eg, nitrogen, oxygen, sulfur, etc.).
[0023] In the present disclosure, the terms "content" and "addition amount" are considered to be substantially the same.
[0024] Since the composition for an electrode according to the present disclosure has the above-mentioned configuration, it is possible to suppress an increase in resistance after high-temperature storage of a battery.
[0025] The electrode composition of the present disclosure is used as a raw material for electrodes. Details of the electrodes will be described later. (1.1) Polymer (A) The electrode composition contains a polymer (A). When the electrode composition contains an active material (B), the polymer (A) adsorbs and / or coats the surface of the active material (B), thereby suppressing the progress of the decomposition reaction of the electrolyte on the surface of the active material (B) when the electrode composition is made into a battery. As a result, the electrode composition can suppress an increase in the resistance of the battery after high-temperature storage.
[0026] The weight average molecular weight of the polymer (A) is not particularly limited, and is preferably 1,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more. The weight average molecular weight of the polymer (A) is preferably 1,000,000 or less, more preferably 800,000 or less, and even more preferably 500,000 or less. The weight average molecular weight can be measured, for example, using a gel permeation chromatograph Alliance GPC-2000 model manufactured by Waters Corporation.
[0027] The content of the polymer (A) relative to the solid content of the electrode composition (hereinafter also referred to as the "content of polymer (A)") is not particularly limited, and is preferably 0.01% by mass to 1.0% by mass. This allows the electrode composition to further suppress an increase in resistance after high-temperature storage of a battery.
[0028] From the viewpoint of further suppressing an increase in resistance after high-temperature storage of the battery, the content of the polymer (A) is more preferably 0.05 mass % to 0.8 mass %, further preferably 0.1 mass % to 0.6 mass %, and particularly preferably 0.2 mass % to 0.4 mass %.
[0029] The "solid content of the electrode composition" refers to the total mass excluding the solvent (D) from the electrode composition when the electrode composition contains the solvent (D) described below, and refers to the total mass of the electrode composition when the electrode composition does not contain the solvent (D). (1.1.1) Structural unit (a) The polymer (A) contains a structural unit (a). The structural unit (a) is derived from a monomer (a).
[0030] Among the monomers (a), examples of compounds having a five-membered nitrogen-containing heterocyclic structure containing an unsaturated bond include vinylimidazole, vinylpyrrole, vinylindole, vinylpyrazole, vinylbenzimidazole, vinyl-1H-indazole, vinylpyrroline, vinylpyrazoline, vinyltriazole, vinyltetrazole, vinyloxazole, vinyloxazoline, vinylisoxazole, vinylisoxazoline, vinylthiazole, and vinylthiazoline.
[0031] Among the monomers (a), examples of the compound having a six-membered nitrogen-containing heterocyclic structure containing an unsaturated bond include vinylquinoline, vinylpyridine, vinylquinoline, and vinyltriazine.
[0032] The monomer (a) may be used alone or in combination of two or more kinds.
[0033] In particular, the structural unit (a) preferably contains a structural unit derived from vinylimidazole, and more preferably is a structural unit derived from vinylimidazole, which allows the electrode composition to further suppress an increase in resistance after high-temperature storage of the battery. (1.1.2) Structural unit (b) The polymer (A) may or may not contain a structural unit (b). The structural unit (b) is derived from a compound (excluding the monomer (a)) (hereinafter also referred to as "monomer (b)") that is copolymerizable with the monomer (a). When the polymer (A) does not contain the structural unit (b), the polymer (A) may be a homopolymer of the monomer (a) (proportion of the structural unit (a): 100 mol%). When the polymer (A) contains the structural unit (b), the polymer (A) may be a copolymer of the monomer (a) and the monomer (b).
[0034] When the electrode composition contains an active material (B), the polymer (A) can adsorb and / or coat the surface of the active material (B) to suppress the progress of the decomposition reaction of the electrolyte on the surface of the active material (B) when the electrode composition is made into a battery. As a result, the electrode composition tends to be able to further suppress the increase in resistance after high-temperature storage of the battery. This is presumably because the polymer (A) further containing the structural unit (b) is more likely to adsorb to the surface of the active material (B) and function as a protective coating layer than when the polymer (A) does not contain the structural unit (b).
[0035] Monomer (b) is not particularly limited as long as it is a compound copolymerizable with monomer (a). Examples of monomer (b) include unsaturated monomers having a carboxyl group and their salts, (meth)acrylic acid alkyl esters, unsaturated monomers having an acidic phosphate ester group, (meth)acrylamide and its derivatives, ether sulfate type ammonium salts, and unsaturated monomers having a carbonyl group.
[0036] Examples of unsaturated monomers having a carboxyl group and salts thereof include (meth)acrylic acid, maleic acid, maleic anhydride, itaconic acid, fumaric acid, crotonic acid, acrylamidoglycolic acid, etc. Examples of salts include alkali metal salts (e.g., sodium, potassium, etc.), alkaline earth metal salts (e.g., calcium, magnesium, etc.), ammonium salts, organic amine salts (monoethanolamine, triethanolamine, etc.), etc.
[0037] Examples of (meth)acrylic acid alkyl esters include hydroxyethyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, (N,N-dimethylaminoethyl) (meth)acrylate, (N,N-diethylaminoethyl) (meth)acrylate, and aminoethyl (meth)acrylate.
[0038] Examples of the unsaturated monomer having an acidic phosphate group include 2-(meth)acryloyloxyethyl acid phosphate, 2-(meth)acryloyloxypropyl acid phosphate, 2-(meth)acryloyloxy-3-chloropropyl acid phosphate, and 2-(meth)acryloyloxyethyl phenyl phosphate.
[0039] Examples of (meth)acrylamide and derivatives thereof include (meth)acrylamide, methylenebis(meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, and N,N-dimethyl(meth)acrylamide.
[0040] The ether sulfate type ammonium salt may be a commercially available product. Examples of commercially available ether sulfate type ammonium salts include products from ADEKA CORPORATION (for example, "SR-10", "SR-020", "SR-1025", and "SR-3025").
[0041] Examples of the unsaturated monomer having a carbonyl group include vinylpyrrolidone, acrolein, diacetone (meth)acrylamide, vinyl methyl ketone, vinyl ethyl ketone, and vinyl butyl ketone.
[0042] The proportion of the structural unit (a) is more than 50 mol%. The proportion of the structural unit (a) is preferably 60 mol% or more. The proportion of the structural unit (a) is more preferably 60 mol% or more and 100 mol% or less, even more preferably 70 mol% or more and less than 100 mol%, particularly preferably 80 mol% or more and less than 100 mol%, more preferably 80 mol% or more and 99 mol% or less, and even more preferably 85 mol% or more and 99 mol% or less. By having the proportion of the structural unit (a) in the above range, the electrode composition can suppress an increase in the resistance of the battery after high-temperature storage more than when the proportion of the structural unit (a) is not in the above range.
[0043] When the polymer (A) does not contain the structural unit (b), the proportion of the structural unit (a) may be 100 mol %.
[0044] When the polymer (A) contains the structural unit (b), the proportion of the structural unit (a) and the proportion of the structural unit (b) in the polymer (A) relative to the total of all structural units constituting the polymer (A) (hereinafter also referred to as the "proportion of structural unit (b)") are preferably in the following ranges.
[0045] From the viewpoint of further suppressing an increase in resistance after high-temperature storage of a battery, the proportion of the structural unit (a) is preferably 60 mol% or more and less than 100 mol%, more preferably 70 mol% or more and less than 100 mol%, even more preferably 80 mol% or more and less than 100 mol%, particularly preferably 80 mol% or more and 99 mol% or less, and more preferably 85 mol% or more and 99 mol% or less.
[0046] The proportion of the structural unit (b) is appropriately selected depending on the type of structural unit (b) (i.e., the type of monomer (b)) and the like. The proportion of the structural unit (b) is preferably more than 0 mol%. From the viewpoint of further suppressing an increase in resistance after high-temperature storage of a battery with the electrode composition, the proportion of the structural unit (b) is preferably more than 0 mol% and not more than 40 mol%, more preferably more than 0 mol% and not more than 30 mol%, even more preferably more than 0 mol% and not more than 20 mol%, particularly preferably 1 mol% or more and not more than 20 mol%, and more preferably 1 mol% or more and not more than 15 mol%. (1.2) Active material (B) The electrode composition may contain an active material (B). This allows the solid of the electrode composition to function as an electrode mixture layer. The "electrode mixture layer" refers to at least one of a negative electrode mixture layer and a positive electrode mixture layer.
[0047] The active material (B) may be either a negative electrode active material (B1) or a positive electrode active material (B2).
[0048] The shape of the active material (B) is not particularly limited, and may be fibrous, spherical, flake, etc. When the active material (B) is particulate, the particle size of the active material (B) is not particularly limited. The particle size of the negative electrode active material (B1) is preferably 5 μm to 20 μm. The particle size of the positive electrode active material (B2) is preferably 5 μm to 15 μm.
[0049] The primary particle size of the particles of the positive electrode active material (B2) is preferably 2.0 μm or less, and more preferably 0.2 μm to 1.0 μm.
[0050] The particle size of the active material (B) is the particle size (particle size distribution D50, median diameter) corresponding to the cumulative 50 volume % from the smaller particle size side in the volume-based particle size distribution measured by a particle size distribution measuring device based on a laser light diffraction scattering method.
[0051] When the electrode composition contains an active material (B), the content of the active material (B) is not particularly limited and is preferably 10 mass% to 99.9 mass%, more preferably 30 mass% to 99 mass%, even more preferably 50 mass% to 99 mass%, and particularly preferably 70 mass% to 99 mass%, based on the solid content of the electrode composition.
[0052] The active material (B) is appropriately selected depending on the type of battery and the application of the electrode composition, and may be a known active material.
[0053] Hereinafter, the active material (B) will be described in the case where the battery is a lithium ion secondary battery and the solid of the electrode composition is used in the electrode mixture layer. (1.2.1) Negative electrode active material (B1) The negative electrode active material (B1) is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions. Examples of the negative electrode active material (B1) include carbon-based compounds, silicon oxides, metals (e.g., silicon, tin, lithium, etc.), alloys (e.g., silicon alloys, tin alloys, lithium alloys, etc.), and lithium titanate.
[0054] The term "carbonaceous compound" refers to a carbonaceous material having a volume resistivity at 20° C. of less than 40 Ω·cm, preferably less than 3 Ω·cm.
[0055] "Silicon oxide" refers to a compound represented by the following formula (1).
[0056] Formula (1): SiO X [In formula (1), X represents 0.5 or more and less than 1.6.] Examples of carbon-based compounds include graphite and amorphous carbon materials. Examples of graphite include artificial graphite and natural graphite (e.g., flake graphite, lump graphite, and amorphous graphite). Examples of amorphous carbon materials include hard carbon, coke, mesocarbon microbeads (MCMB) fired at 1500° C. or less, and mesophase pitch carbon fiber (MCF).
[0057] The silicon oxide may be coated with amorphous carbon. The silicon oxide may be a known compound. For silicon oxide, WO 2013 / 094668, JP 2016-143642, etc. may be referred to as appropriate.
[0058] The negative electrode active material (B1) may be used alone or in combination of two or more kinds.
[0059] Among them, the negative electrode active material (B1) preferably contains a carbon-based compound, and more preferably is a carbon-based compound, which allows the battery to have both high energy density and high charge-discharge cycle durability, as compared to a case in which the negative electrode active material (B1) does not contain a carbon-based compound. (1.2.2) Positive electrode active material (B2) The positive electrode active material (B2) is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions, and can be appropriately adjusted depending on the application of the lithium ion secondary battery.
[0060] Examples of the positive electrode active material (B2) include a first oxide and a second oxide.
[0061] The first oxide contains lithium (Li) and nickel (Ni) as constituent metal elements.
[0062] The second oxide contains Li, Ni, and at least one metal element other than Li and Ni as constituent metal elements. Examples of metal elements other than Li and Ni include transition metal elements and typical metal elements. The second oxide preferably contains the metal elements other than Li and Ni in an amount equivalent to or less than Ni in terms of atomic number. The metal elements other than Li and Ni may be, for example, at least one selected from the group consisting of Co, Mn, Al, Cr, Fe, V, Mg, Ca, Na, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, and Ce.
[0063] The positive electrode active material (B2) may be used alone or in combination of two or more kinds.
[0064] The positive electrode active material (B2) preferably contains a lithium-containing composite oxide (hereinafter, sometimes referred to as "NCM") represented by the following formula (X). The lithium-containing composite oxide (X) has the advantages of high energy density per unit volume and excellent thermal stability.
[0065] LiNi a Co b Mn c O 2 … Formula (X) In formula (X), a, b and c each independently represent more than 0 and less than 1, and the sum of a, b and c is 0.99 or more and 1.00 or less.
[0066] A specific example of NCM is LiNi 0.33 Co 0.33 Mn 0.33 O 2 , LiNi 0.5 Co 0.3 Mn 0.2 O 2 , LiNi 0.5 Co 0.2 Mn 0.3 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiNi 0.8 Co0.1 Mn 0.1 O 2 etc.
[0067] The positive electrode active material (B2) may contain a lithium-containing composite oxide (hereinafter sometimes referred to as "NCA") represented by the following formula (Y).
[0068] Li t Ni 1-x-y Co x Al y O 2 … Expression (Y) In formula (Y), t is 0.95 or more and 1.15 or less, x is 0 or more and 0.3 or less, y is 0.01 or more and 0.2 or less, and the sum of x and y is less than 0.5.
[0069] A specific example of NCA is LiNi 0.8 Co 0.15 Al 0.05 O 2 etc. (1.3) Binder (C) The electrode composition may contain a binder (C), whereby, when the electrode composition contains an active material (B) and forms an electrode mixture layer on a current collector, the binder (C) can bind the active material (B) to the electrode current collector.
[0070] Examples of the binder (C) include carboxymethyl cellulose (CMC), polyvinyl acetate, polymethyl methacrylate, nitrocellulose, fluororesin, and rubber particles.
[0071] Examples of the fluororesin include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), vinylidene fluoride-hexafluoropropylene copolymer, and the like.
[0072] Examples of the rubber particles include styrene butadiene rubber (SBR) particles and acrylonitrile rubber particles.
[0073] The binder (C) may be used alone or in combination of two or more kinds.
[0074] When the composition for an electrode contains a binder (C), the content of the binder (C) is not particularly limited, and is preferably 0.1% by mass to 4% by mass based on the solid content of the composition for a battery. (1.4) Solvent (D) The electrode composition may contain a solvent (D).
[0075] Examples of the solvent (D) include water and liquid media compatible with water. When the solvent (D) contained in the electrode composition includes a liquid medium compatible with water, the coating property of the electrode composition on the electrode current collector is improved. Examples of the liquid medium compatible with water include alcohols, glycols, cellosolves, amino alcohols, amines, ketones, amides (e.g., N-methylpyrrolidone, etc.), carboxylic acid amides, phosphoric acid amides, sulfoxides, carboxylic acid esters, phosphoric acid esters, ethers, and nitriles. When the electrode composition includes the positive electrode active material (B2) and the solvent (D), it is preferable to use N-methylpyrrolidone as the solvent (D).
[0076] When the electrode composition contains a solvent (D), the ratio of the total amount of solids to the total amount of the electrode composition (hereinafter also referred to as "solids concentration") is not particularly limited, and is preferably 30 mass% or more, more preferably 35 mass% or more, and even more preferably 40 mass% or more. The solids concentration is preferably 95 mass% or less, more preferably 90 mass% or less, even more preferably 80 mass% or less, and particularly preferably 70 mass% or less. (1.5) Conductive additive (E) The electrode composition may contain a conductive assistant (E).
[0077] The conductive assistant (E) may be a known conductive assistant. As the known conductive assistant, a conductive carbon material is preferable. As the conductive carbon material, carbon black, conductive carbon fiber, fullerene, etc. are mentioned. As the conductive carbon fiber, carbon nanotube, carbon nanofiber, carbon fiber, etc. are mentioned. As the natural graphite, for example, flake graphite, lump graphite, earthy graphite, etc. are mentioned.
[0078] The conductive assistant (E) may be used alone or in combination of two or more kinds.
[0079] The conductive assistant (E) may be a commercially available product. Examples of commercially available carbon black products include "Super P" (manufactured by TIMCAL). Examples of commercially available flake graphite products include "KS-6" (manufactured by TIMREX).
[0080] The content of the conductive assistant (E) is not particularly limited, and is preferably 0.05% by mass to 5% by mass based on the solid content of the electrode composition. (1.6) Additives (F) The electrode composition may contain an additive (F). This allows the electrode composition to have various functions depending on the type of additive (F). Examples of the additive (F) include a thickener, a surfactant, a dispersant, a wetting agent, and an antifoaming agent. (1.7) Preferred composition The composition for an electrode preferably contains, in addition to the polymer (A), an active material (B) and a binder (C), so that the solid content of the composition for an electrode functions as an electrode mixture layer of a battery.
[0081] When the electrode composition further contains an active material (B) and a binder (C), the active material (B) preferably contains a carbon-based compound, more preferably is a carbon-based compound. By containing a carbon-based compound in the active material (B), the active material (B) can achieve both high energy density and charge-discharge cycle durability of the battery, compared to a case where the active material (B) does not contain a carbon-based compound. (2) Electrode The electrode of the present disclosure includes a current collector and a solid material of the electrode composition of the present disclosure.
[0082] An "electrode" refers to at least one of the positive and negative electrodes of a battery.
[0083] The term "solid electrode composition" refers to a composition that is in a solid state at room temperature (23°C) and from which the solvent (D) has been removed when the electrode composition contains a solvent (D), and refers to a composition that is in a solid state at room temperature (23°C) and is made of the electrode composition when the electrode composition does not contain a solvent (D). When the electrode composition contains a solvent (D), the solid electrode composition is formed, for example, by applying the electrode composition to a current collector and drying it. When the electrode composition does not contain a solvent (D), the solid electrode composition is formed, for example, by applying a molten electrode composition to a current collector and cooling it.
[0084] Since the electrode of the present disclosure has the above-mentioned configuration, it is possible to suppress an increase in resistance after high-temperature storage of a battery.
[0085] The solid material of the electrode layer composition may be formed on at least one of the main surfaces of the current collector.
[0086] The function of the solid material of the electrode composition depends on the raw material of the electrode composition. When the electrode composition contains an active material (B), the solid material of the electrode composition may function as an electrode mixture layer. When the electrode composition does not contain an active material (B), the solid material of the electrode composition may function as an undercoat layer interposed between the current collector and the electrode mixture layer. Hereinafter, the case where the solid material of the electrode composition functions as an electrode mixture layer will be described. (2.1) Negative electrode The negative electrode includes a current collector (hereinafter also referred to as a "negative electrode current collector") and a negative electrode mixture layer. The negative electrode mixture layer is formed on at least one of the main surfaces of the negative electrode current collector.
[0087] Examples of the material for the negative electrode current collector include copper, aluminum, nickel, stainless steel (SUS), and nickel-plated steel.
[0088] The negative electrode mixture layer is a solid material of the electrode composition of the present disclosure. Specifically, the negative electrode mixture layer preferably contains a polymer (A), a negative electrode active material (B1), and a binder (C). The negative electrode mixture layer may further contain at least one of a conductive assistant (E) and an additive (F) as necessary. (2.2) Positive electrode The positive electrode includes a current collector (hereinafter also referred to as a "positive electrode current collector") and a positive electrode mixture layer. The positive electrode mixture layer is formed on at least one of the main surfaces of the positive electrode current collector.
[0089] Examples of the material of the positive electrode current collector include aluminum, nickel, stainless steel (SUS), copper, etc. "Aluminum" includes pure aluminum and aluminum alloys.
[0090] The positive electrode mixture layer is a solid material of the electrode composition of the present disclosure. More specifically, the positive electrode mixture layer preferably contains a polymer (A), a positive electrode active material (B2), and a binder (C). The positive electrode mixture layer may further contain at least one of a conductive assistant (E) and an additive (F) as necessary. (3)Battery The battery of the present disclosure comprises the electrode of the present disclosure.
[0091] Since the battery of the present disclosure has the above configuration, an increase in resistance after high-temperature storage is suppressed.
[0092] In the battery of the present disclosure, the electrode of the present disclosure is at least one of a positive electrode and a negative electrode. The type of the battery is not particularly limited and is appropriately selected according to the application of the battery. Examples of the type of the battery include a lithium ion secondary battery, a manganese battery, a nickel-hydrogen battery, a nickel-cadmium battery, a nickel-zinc battery, a sodium-sulfur battery, a zinc-halogen battery, and a redox flow battery.
[0093] Hereinafter, a lithium ion secondary battery will be described as an example of the battery of the present disclosure. (3.1) Lithium-ion secondary battery A lithium ion secondary battery comprises the electrodes of the present disclosure.
[0094] A lithium ion secondary battery generally includes an exterior body, a positive electrode, a negative electrode, a separator, and an electrolyte. The exterior body accommodates the positive electrode, the negative electrode, the separator, and the non-aqueous electrolyte. The separator separates the positive electrode and the negative electrode.
[0095] In the lithium ion secondary battery of the present disclosure, at least one of the positive electrode and the negative electrode is the electrode of the present disclosure. When one of the positive electrode and the negative electrode of the lithium ion secondary battery of the present disclosure is the electrode of the present disclosure, the other of the positive electrode and the negative electrode may be a known electrode used in lithium ion secondary batteries.
[0096] Hereinafter, a case where the positive electrode and the negative electrode are the electrodes of the present disclosure will be described. (3.1.1) Exterior Body The shape of the exterior body is not particularly limited and may be appropriately selected depending on the application of the lithium ion secondary battery, etc. Examples of the exterior body include an exterior body including a laminate film and an exterior body consisting of a battery can and a battery can lid. (3.1.2) Positive and negative electrodes The positive electrode is the positive electrode of the present disclosure. The negative electrode is the negative electrode of the present disclosure. (3.1.3) Separators The separator may be, for example, a porous resin plate. The material of the porous resin plate may be a resin or a nonwoven fabric containing the resin. The resin may be polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), polyester, cellulose, polyamide, or the like. Among them, the separator is preferably a porous resin sheet having a single layer or multilayer structure. The material of the porous resin sheet is mainly composed of one or more polyolefin resins. The thickness of the separator is preferably 5 μm or more and 30 μm or less. The separator is preferably disposed between the positive electrode and the negative electrode. (3.1.4) Non-aqueous electrolyte The non-aqueous electrolyte contains an electrolyte and a non-aqueous solvent. (3.1.4.1) Electrolyte The electrolyte preferably contains at least one of a fluorine-containing lithium salt (hereinafter sometimes referred to as a "fluorine-containing lithium salt") and a fluorine-free lithium salt.
[0097] Examples of the fluorine-containing lithium salt include inorganic acid anion salts and organic acid anion salts.
[0098] Examples of inorganic acid anion salts include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium tantalate hexafluoro(LiTaF 6 ), etc.
[0099] Examples of organic acid anion salts include lithium trifluoromethanesulfonate (LiCF 3 SO 3 Among them, the fluorine-containing lithium salt is LiPF 6 is particularly preferred.
[0100] Lithium salts that do not contain fluorine include lithium perchlorate (LiClO 4 ), lithium aluminum tetrachloride (LiAlCl 4 ), lithium decachlorodecaborate (Li 2 B 10 Cl 10 ) etc.
[0101] When the electrolyte contains a fluorine-containing lithium salt, the content of the fluorine-containing lithium salt is preferably 50 mass % or more and 100 mass % or less, more preferably 60 mass % or more and 100 mass % or less, and even more preferably 80 mass % or more and 100 mass % or less, based on the total amount of the electrolyte.
[0102] The fluorine-containing lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium hexafluorophosphate (LiPF 6 The content of ) is preferably 50% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on the total amount of the electrolyte.
[0103] When the non-aqueous electrolyte contains an electrolyte, the concentration of the electrolyte in the non-aqueous electrolyte is preferably 0.1 mol / L or more and 3 mol / L or less, and more preferably 0.5 mol / L or more and 2 mol / L or less.
[0104] The non-aqueous electrolyte is lithium hexafluorophosphate (LiPF 6 ), the lithium hexafluorophosphate (LiPF 6 The concentration of ) is preferably 0.1 mol / L or more and 3 mol / L or less, more preferably 0.5 mol / L or more and 2 mol / L or less. (3.1.4.2) Nonaqueous solvents The non-aqueous electrolyte generally contains a non-aqueous solvent.
[0105] Examples of non-aqueous solvents include cyclic carbonates, fluorine-containing cyclic carbonates, chain carbonates, fluorine-containing chain carbonates, aliphatic carboxylic acid esters, fluorine-containing aliphatic carboxylic acid esters, γ-lactones, fluorine-containing γ-lactones, cyclic ethers, fluorine-containing cyclic ethers, chain ethers, fluorine-containing chain ethers, nitriles, amides, lactams, nitromethane, nitroethane, sulfolane, trimethyl phosphate, dimethyl sulfoxide, dimethyl sulfoxide phosphate, etc. The non-aqueous solvents may be used alone or in combination of two or more.
[0106] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC).
[0107] Examples of fluorine-containing cyclic carbonates include fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoropropylene carbonate, and the like.
[0108] Examples of chain carbonates include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and dipropyl carbonate (DPC).
[0109] Examples of the fluorine-containing chain carbonates include methyl 2,2,2-trifluoroethyl carbonate.
[0110] Examples of aliphatic carboxylate esters include methyl formate, methyl acetate, methyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylbutyrate, ethyl formate, ethyl acetate, ethyl propionate, ethyl butyrate, ethyl isobutyrate, and ethyl trimethylbutyrate.
[0111] Examples of the fluorine-containing aliphatic carboxylate esters include methyl difluoroacetate, methyl 3,3,3-trifluoropropionate, ethyl difluoroacetate, and 2,2,2-trifluoroethyl acetate.
[0112] Examples of γ-lactones include γ-butyrolactone and γ-valerolactone.
[0113] Examples of cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, and 1,4-dioxane.
[0114] Examples of chain ethers include 1,2-ethoxyethane (DEE), ethoxymethoxyethane (EME), diethyl ether, 1,2-dimethoxyethane, and 1,2-dibutoxyethane.
[0115] Examples of fluorine-containing chain ethers include HCF 2 CF 2 CH 2 OCF 2 CF 2 H, C.F. 3 CF 2 CH 2 OCF 2 CF 2 H, HCF 2 CF 2 CH 2 OCF 2 CFHCF 3 , C.F. 3 CF 2 CH 2 OCF 2 CFHCF 3 , C 6 F 13 OCH 3 , C 6 F 13 O.C. 2 H 5 , C 8 F 17 OCH 3 , C 8 F 17 O.C. 2 H 5 , C.F. 3 CFHCF 2 CH(CH 3 )OCF 2 CFHCF 3 , H.C.F. 2 CF 2 OCH(C 2 H 5 ) 2 , H.C.F. 2 CF 2 O.C. 4 H 9 , H.C.F. 2 CF 2 OCH 2 CH(C 2 H 5 ) 2 , H.C.F.2 CF 2 OCH 2 CH(CH 3 ) 2 , etc.
[0116] Examples of nitriles include acetonitrile, glutaronitrile, adiponitrile, methoxyacetonitrile, and 3-methoxypropionitrile.
[0117] The amides include, for example, N,N-dimethylformamide.
[0118] Examples of lactams include N-methylpyrrolidinone, N-methyloxazolidinone, and N,N'-dimethylimidazolidinone.
[0119] The non-aqueous solvent preferably contains at least one selected from the group consisting of cyclic carbonates, fluorine-containing cyclic carbonates, chain carbonates, and fluorine-containing chain carbonates. In this case, the total proportion of the cyclic carbonates, fluorine-containing cyclic carbonates, chain carbonates, and fluorine-containing chain carbonates is preferably 50% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on the total amount of the non-aqueous solvent.
[0120] The non-aqueous solvent preferably contains at least one selected from the group consisting of cyclic carbonates and chain carbonates. In this case, the total proportion of the cyclic carbonates and chain carbonates in the non-aqueous solvent is preferably 50% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on the total amount of the non-aqueous solvent.
[0121] The content of the non-aqueous solvent is preferably 99 mass % or less, more preferably 97 mass % or less, and further preferably 90 mass % or less, based on the total amount of the non-aqueous electrolyte.
[0122] The content of the non-aqueous solvent is preferably 60 mass % or more, and more preferably 70 mass % or more, based on the total amount of the non-aqueous electrolyte.
[0123] The intrinsic viscosity of the nonaqueous solvent is preferably 10.0 mPa·s or less at 25° C., from the viewpoint of further improving the dissociation property of the electrolyte and the mobility of ions. (3.1.4.3) Electrolyte Additives The non-aqueous solvent may contain an electrolyte additive. This makes it possible to make it difficult for side reactions that are not the original battery reaction to proceed during the charge / discharge cycle of the lithium ion secondary battery. The battery reaction is a reaction in which lithium ions enter and leave (intercalate) the positive electrode and the negative electrode. The side reactions include a reductive decomposition reaction of the non-aqueous electrolyte by the negative electrode, an oxidative decomposition reaction of the non-aqueous electrolyte by the positive electrode, and elution of metal elements in the positive electrode active material.
[0124] The electrolyte additive is not particularly limited, and any known additive can be used. For example, the additives described in JP-A-2019-153443 can be used. (3.2) An example of a lithium-ion secondary battery An example of a lithium ion secondary battery according to an embodiment of the present disclosure will be specifically described with reference to Fig. 1. Fig. 1 is a cross-sectional view of a lithium ion secondary battery 1 according to an embodiment of the present disclosure.
[0125] The lithium ion secondary battery 1 according to the embodiment of the present disclosure is a laminated type. As shown in FIG. 1, the lithium ion secondary battery 1 includes a battery element 10, a positive electrode lead 21, a negative electrode lead 22, and an exterior body 30. The battery element 10 is enclosed inside the exterior body 30. The exterior body 30 is formed of a laminate film. The positive electrode lead 21 and the negative electrode lead 22 are attached to the battery element 10. The positive electrode lead 21 and the negative electrode lead 22 are led out in opposite directions from the inside to the outside of the exterior body 30.
[0126] 1, the battery element 10 is formed by laminating a positive electrode 11, a separator 13, and a negative electrode 12. The positive electrode 11 is formed by forming a positive electrode mixture layer 11B on both main surfaces of a positive electrode current collector 11A. The negative electrode 12 is formed by forming a negative electrode mixture layer 12B on both main surfaces of a negative electrode current collector 12A.
[0127] As shown in FIG. 1, a positive electrode composite layer 11B formed on one main surface of a positive electrode current collector 11A of a positive electrode 11 and a negative electrode composite layer 12B formed on one main surface of a negative electrode current collector 12A of a negative electrode 12 adjacent to the positive electrode 11 face each other via a separator 13.
[0128] A non-aqueous electrolyte is injected into the interior of the exterior body 30. The non-aqueous electrolyte permeates the positive electrode mixture layer 11B, the separator 13, and the negative electrode mixture layer 12B. In the lithium-ion secondary battery 1, one unit cell layer 14 is formed by the adjacent positive electrode mixture layer 11B, the separator 13, and the negative electrode mixture layer 12B.
[0129] In this embodiment, the lithium ion secondary battery 1 is a laminated type, but the present disclosure is not limited thereto, and the lithium ion secondary battery 1 may be, for example, a wound type. The wound type is formed by stacking a positive electrode, a separator, a negative electrode, and a separator in this order and winding them into a layered shape. The wound type includes a cylindrical type and a rectangular type.
[0130] 1, the directions in which the positive electrode lead 21 and the negative electrode lead 22 protrude from the inside of the exterior body 30 to the outside are opposite directions relative to the exterior body 30, but the present disclosure is not limited thereto. For example, the directions in which the positive electrode lead and the negative electrode lead protrude from the inside of the exterior body 30 to the outside may be the same direction relative to the exterior body 30. EXAMPLES
[0131] Examples of the present disclosure will be described below, but the present disclosure is not limited to the following examples. In the following, "addition amount" means the content relative to the total amount of the finally obtained nonaqueous electrolyte, and "wt%" means mass%.
[0132] [1] Polymerization example [1.1] Polymerization Example 1 (Polyvinylpyrrolidone homopolymer) A reaction vessel equipped with a stirrer, a reflux condenser, a dropping device, and a thermometer was prepared. 75 parts by mass of 1-vinylpyrrolidone as monomer (x) and 75 parts by mass of distilled water were mixed to prepare an aqueous monomer solution. 309.5 parts by mass of distilled water was charged into the reaction vessel, and the temperature was raised to 80°C while stirring and replacing with nitrogen. The internal temperature was kept at 80°C, 1.3 parts by mass of 4,4'-azobis(4-cyanovaleric acid) was added as a polymerization initiator, and the aqueous monomer solution was continuously dropped into the reactor over 2 hours. After the dropwise addition, the mixture was aged for 6 hours. The aqueous solution obtained was cooled to room temperature, and then distilled water was added to the aqueous solution to obtain an aqueous polymer solution. The solid content concentration of the aqueous polymer solution was 14.8% by weight.
[0133] The aqueous polymer solution of Polymerization Example 1 contained a polyvinylpyrrolidone homopolymer. 1-vinylpyrrolidone, which is the monomer (b) of the polyvinylpyrrolidone homopolymer, does not have a five- or six-membered nitrogen-containing heterocyclic structure containing an unsaturated bond. [1.2] Polymerization Example 2 (Polyvinylimidazole homopolymer) An aqueous polymer solution was obtained in the same manner as in Polymerization Example 1, except that 1-vinylpyrrolidone was changed to 1-vinylimidazole as the monomer (a).
[0134] The aqueous polymer solution of Polymerization Example 2 contained polyvinylimidazole homopolymer as the polymer (A). 1-vinylimidazole, which is the monomer (a) of the polyvinylimidazole homopolymer, has a five-membered nitrogen-containing heterocyclic structure containing an unsaturated bond. Therefore, the polyvinylimidazole homopolymer of Polymerization Example 2 has a structural unit (a). [1.3] Polymerization Example 3 (Polyvinylimidazole homopolymer) A reaction vessel equipped with a stirrer, a reflux condenser, a dropping device, and a thermometer was prepared. 75 parts by mass of 1-vinylimidazole as monomer (a) and 75 parts by mass of distilled water were mixed to prepare an aqueous monomer solution. 279.5 parts by mass of distilled water and 2.5 parts by mass of a 35% aqueous hydrochloric acid solution were charged into a reaction vessel, and the temperature was raised to 80°C while stirring and replacing with nitrogen. The internal temperature was kept at 80°C, 1.3 parts by mass of 4,4'-azobis(4-cyanovaleric acid) was added as a polymerization initiator, and the aqueous monomer solution was continuously dropped into the reactor over 2 hours. After the dropwise addition, the mixture was aged for 6 hours. The aqueous solution obtained was cooled to room temperature, and then distilled water was added to the aqueous solution to obtain an aqueous polymer solution. The solid content concentration of the aqueous polymer solution was 14.8% by weight.
[0135] The aqueous polymer solution of Polymerization Example 3 contained a polyvinylimidazole homopolymer as the polymer (A). Therefore, the polyvinylimidazole homopolymer of Polymerization Example 3 has a structural unit (a). [1.4] Polymerization Example 4 (Polyvinylimidazole Copolymer) A reaction vessel equipped with a stirrer, a reflux condenser, a dropping device, and a thermometer was prepared. 67.5 parts by mass of 1-vinylimidazole as monomer (a), 7.5 parts by mass of 2-hydroxyethyl methacrylate as monomer (b), and 75 parts by mass of distilled water were mixed to prepare an aqueous monomer solution. 309.5 parts by mass of distilled water was charged into the reaction vessel, and the temperature was raised to 80°C while stirring and replacing with nitrogen. The internal temperature was kept at 80°C, 1.3 parts by mass of 4,4'-azobis(4-cyanovaleric acid) was added as a polymerization initiator, and the aqueous monomer solution was continuously dropped into the reactor over 2 hours. After the dropwise addition, the mixture was aged for 6 hours. The aqueous solution obtained was cooled to room temperature, and then distilled water was added to the aqueous solution to obtain an aqueous polymer solution. The solid content concentration of the aqueous polymer solution was 14.8% by weight.
[0136] The aqueous polymer solution of Polymerization Example 3 contained a polyvinylimidazole copolymer as the polymer (A). 1-vinylimidazole, which is the monomer (a) of the polyvinylimidazole copolymer, has a five-membered nitrogen-containing heterocyclic structure containing an unsaturated bond. Therefore, the polyvinylimidazole copolymer of Polymerization Example 4 has a structural unit (a). [1.5] Polymerization Examples 5 to 12 (Polyvinylimidazole Copolymer) A water-soluble polymer was obtained in the same manner as in Polymerization Example 4, except that 2-hydroxyethyl methacrylate as monomer (b) was changed to monomer (b) shown in Table 1, and the ratio of monomer (a) to monomer (b) was changed to the ratio shown in Table 1.
[0137] The aqueous polymer solution of Polymerization Example 5 contained a polyvinylimidazole copolymer. 1-vinylimidazole, which is the monomer (a) of the polyvinylimidazole copolymer, has a five-membered nitrogen-containing heterocyclic structure containing an unsaturated bond, but the proportion of the monomer (a) was not more than 50%.
[0138] The aqueous polymer solutions of Polymerization Examples 6 to 12 contained polyvinylimidazole copolymers as polymers (A). 1-vinylimidazole, which is the monomer (a) of the polyvinylimidazole copolymers, has a five-membered nitrogen-containing heterocyclic structure containing an unsaturated bond. Therefore, the polyvinylimidazole copolymers of Polymerization Examples 5 to 12 have the structural unit (a). [2] Example 1 [2.1] Electrode composition A 5 L Planetary Disperser was used to prepare the slurry.
[0139] 960 parts by mass of natural graphite as the negative electrode active material (B1) and "Super-P" (material: conductive carbon, BET specific surface area: 62 m) as the conductive assistant material (E). 2To 10 parts by mass of carboxymethylcellulose (CMC) (wt. / g), 450 parts by mass of binder (C) and "1%-CMC aqueous solution" as solvent (D) were added and mixed for 30 minutes to obtain a mixture. "1% by mass aqueous solution of carboxymethylcellulose (CMC)" refers to an aqueous solution in which the ratio of the mass of CMC as binder (C) to the total amount of the aqueous solution is 1% by mass.
[0140] To the obtained mixture, 300 parts by mass of a 1% CMC aqueous solution was added and kneaded for 30 minutes, and then 250 parts by mass of a 1% CMC aqueous solution was added and kneaded for 30 minutes.
[0141] To the obtained mixture, the polymer (A) and 200 parts by mass of the aqueous polymer solution of Polymerization Example 2 as the solvent (D) were added, and the mixture was kneaded for 30 minutes.
[0142] To the obtained kneaded product, 50 parts by mass of styrene butadiene rubber (SBR) (40% emulsion) as a binder (C) was added, mixed for 30 minutes, and then vacuum degassed for 30 minutes. This resulted in a negative electrode mixture slurry (i.e., a composition for electrodes). The solid content of the negative electrode mixture slurry was 44%. [2.2] Lithium-ion secondary battery (laminated battery) As a lithium ion secondary battery, a stacked battery for evaluating the heat generation rate was fabricated in the following manner. [2.2.1] Negative electrode A die coater was used for applying the slurry.
[0143] The coating mass after drying is 11.0mg / cm 2 The negative electrode mixture slurry was applied to a part of one side of a copper foil (thickness: 10 μm) serving as a negative electrode current collector, and then dried. Next, a coating mass of 11.0 mg / cm was applied to a part of the opposite side (uncoated side) of the copper foil. 2 The negative electrode mixture slurry was applied and dried so that
[0144] The double-sided coated copper foil obtained in this way (the total coating amount on both sides is 22.0 mg / cm 2 ) was dried in a vacuum drying oven at 120°C for 12 hours.
[0145] After drying, the double-sided coated copper foil was pressed in a small press until the density reached 1.45±0.05g / cm 3 It was pressed to be.
[0146] The electrode was slit to provide an electrode coating area (31 mm x 42 mm) and a tab welding margin.
[0147] The double-sided coated copper foil after pressing was slit to obtain a coated portion (42 mm x 31 mm) and a tab welding margin, thereby obtaining a negative electrode. [2.2.2] Positive electrode A 5 L Planetary Disperser was used to prepare the slurry.
[0148] NMC532 (i.e., LiNi 0.5 Mn 0.3 Co 0.2 O 2 A mixture of 920 parts by mass of "Super-P" (conductive carbon manufactured by TIMCAL) as a conductive additive, and 20 parts by mass of "KS-6" (flake graphite manufactured by TIMREX) as a conductive additive was mixed for 10 minutes, and then 100 parts by mass of N-methylpyrrolidone (NMP) was added and mixed for a further 20 minutes.
[0149] Next, 150 parts by mass of "8%-PVDF solution" (PVDFW#7200 manufactured by Kureha Corporation dissolved in NMP) was added and kneaded for 30 minutes, and then 150 parts by mass of the 8%-PVDF solution was added and kneaded for 30 minutes. "8%-PVDF solution" refers to a solution in which the mass ratio of PVDF (PVDF "W#7200" manufactured by Kureha Corporation) to the total amount of PVDF solution (solution: NMP) is 8%. Then, 200 parts by mass of the 8%-PVDF solution was added and kneaded for 30 minutes. Next, 80 parts by mass of the solution dissolved in NMP was added and kneaded for 30 minutes. Then, 27 parts by mass of NMP was added to adjust the viscosity and mixed for 30 minutes, followed by vacuum degassing for 30 minutes.
[0150] As a result, a positive electrode mixture slurry with a solid content of 60% was obtained.
[0151] A die coater was used for applying the slurry.
[0152] The coating mass after drying is 19.0mg / cm 2 The positive electrode mixture slurry was applied to a portion of one side of an aluminum foil (thickness: 20 μm, width: 200 mm) serving as a positive electrode current collector, and then dried. Next, a coating mass of 19.0 mg / cm was similarly applied to a portion of the opposite side (uncoated side). 2 The positive electrode mixture slurry was applied to an aluminum foil so as to become a thickness of 100 μm and then dried.
[0153] The thus obtained double-sided coated aluminum foil (the total coating amount on both sides is 38.0 mg / cm 2 ) was dried in a vacuum drying oven at 130°C for 12 hours.
[0154] The double-sided coated aluminum foil after drying was pressed in a 35-ton press to a press density of 2.9±0.05g / cm 3 It was pressed to be.
[0155] The double-sided coated aluminum foil after pressing was slit so as to obtain a coated portion (40 mm×29 mm) and a tab welding margin, thereby obtaining a positive electrode. [2.2.3] Non-aqueous electrolyte Ethylene carbonate (hereinafter, EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of EC:EMC=30:70 to obtain a mixed solvent as a non-aqueous solvent.
[0156] In the above mixed solvent, LiPF as an electrolyte 6 was dissolved so that the concentration in the finally obtained non-aqueous electrolyte was 1 mol / liter (hereinafter, also referred to as "1M"). Next, vinylene carbonate (VC) as an additive was dissolved so that the content in the finally obtained non-aqueous electrolyte was 0.5 mass%. Thus, a non-aqueous electrolyte was obtained. [2.2.4] Stacked battery precursor As a separator, a polyethylene porous film (50 mm×50 mm) with a porosity of 45% and a thickness of 25 μm was prepared.
[0157] The negative electrode (front surface), separator, positive electrode (rear surface / front surface), separator, and negative electrode (front surface) were stacked and fixed in order to obtain a laminate having 5 layers of positive electrodes and 6 layers of negative electrodes. An aluminum tab was bonded as a positive electrode tab to the margin of the positive electrode of the obtained laminate using an ultrasonic bonding machine, and a nickel tab was bonded as a negative electrode tab to the margin of the negative electrode using an ultrasonic bonding machine. The laminate with the bonded positive electrode tab and negative electrode tab was sandwiched between laminate sheets, and three sides were heat sealed to obtain a laminated laminated battery precursor. The battery capacity of the battery precursor was 350 mAh in terms of discharge capacity.
[0158] The inside of the laminate obtained above was dried under reduced pressure for 12 hours at 70° C. in a vacuum dryer. After the reduced pressure drying, 1.20±0.05 parts by mass of the nonaqueous electrolyte was injected into the remaining side of the laminate not heat-sealed, and the remaining side was then heat-sealed while drawing a vacuum to obtain a stacked battery precursor (i.e., a stacked battery before being charged and discharged). [2.2.5] Stacked battery The laminated battery precursor was kept in the atmosphere at 25° C. for 24 hours, then charged at a constant current of 0.1 C (0.1C-CC) for 3 hours, and then allowed to rest at 25° C. for 12 hours.
[0159] Next, the stacked battery precursor after resting was charged at a constant current and constant voltage of 0.1C (0.1C-CCCV) to 4.2V (SOC 100%), rested for 30 minutes, and then discharged at a constant current of 0.1C (0.1C-CC) to 2.8V to obtain a stacked battery. [2.3] Evaluation [2.3.1] Battery resistance after high temperature storage (relative value) The stacked battery was evaluated for battery resistance as follows.
[0160] The battery was charged to a constant voltage of 4.2 V at room temperature, and then discharged at a constant current of 0.1 C at room temperature, and the first potential drop was measured for 10 seconds from the start of discharge.
[0161] Similarly, the battery after the activation treatment was charged to a constant voltage of 4.2 V at room temperature, then discharged at a constant current of 0.2 C at room temperature, and the second potential drop was measured for 10 seconds from the start of discharge.
[0162] The activated battery was charged to a constant voltage of 4.2 V at room temperature, and then discharged at a constant current of 0.5 C at room temperature, and the amount of decrease in the third potential was measured for 10 seconds from the start of discharge.
[0163] The activated battery was charged to a constant voltage of 4.2 V at room temperature, and then discharged at a constant current of 1.0 C at room temperature, and the amount of fourth potential drop was measured for 10 seconds from the start of discharge.
[0164] The battery resistance (direct current resistance; DC-IR) at the beginning of discharge was calculated from the first potential drop amount to the fourth potential drop amount when discharging at each current rate.
[0165] The stacked battery was evaluated as follows.
[0166] The battery was charged to a constant voltage of 4.2 V at room temperature and stored in a thermo-hygrostat at 60° C. for 28 days.
[0167] After storage, the battery was taken out and left to stand at room temperature for 2 hours, and then the battery resistance (direct current resistance; DC-IR) was evaluated.
[0168] The rate of increase in battery resistance was calculated from the battery resistance before and after storage.
[0169] The resistance increase rate of Example 1 was calculated as the resistance increase rate after storage (relative value) when the resistance increase rate of Comparative Example 1 obtained below was set to 100. An acceptable resistance increase rate after storage (relative value) is less than 100. [2.3.2] Nail penetration test (relative value) The laminated battery was subjected to the following nail penetration test to evaluate the heat generation rate inside the battery when a short circuit occurred.
[0170] The laminated battery prepared above was charged at 0.1C with a constant current and constant voltage (0.1C-CCCV) to 4.2V (SOC 100%) and subjected to a nail penetration test. A nail having a diameter of 3 mm, a length of 15 mm, a tip angle of 30°, and a bottomed hole with a diameter of 0.6 mm was covered with Macol (registered trademark). Next, a sheath type K thermocouple (product number: IP10-K-0.5-200) with a sheath diameter of 0.5 mm and a sheath length of 200 mm was inserted to a position near the tip of the nail to obtain a nail penetration test tool.
[0171] The nail test tool and the stacked battery were fixed to a nail penetration test device (TYS-94DM45 manufactured by Toyo Systems), and the nail was inserted into the center of the battery (cell) at a speed of 1 mm / sec, shorting the positive and negative electrodes inside the battery container. The temperature inside the battery measured by the nail penetration test tool and the surface temperature obtained from a thermocouple attached to the surface of the battery were measured over time.
[0172] The heat generation rate of the battery was calculated as shown below from the measurement results of the nail penetration test described above. The time when the internal temperature of the battery rose by 0.2°C after short circuit was defined as the heat generation start time T0 (seconds), and 1 second after T0 was defined as T1 (seconds). The internal temperature of the battery at T0 was defined as H0 (°C), and the internal temperature of the battery at T1 was defined as H1 (°C), and the heat generation rate immediately after short circuit was calculated using the following formula.
[0173] Heat release rate = (H1-H0) / (T1-T0) The heat release rate of Example 1 was calculated based on the heat release rate of Comparative Example 1 obtained below taken as 100, and this was used as a nail penetration test value (relative value). [3] Examples 2 to 11 and Comparative Examples 1 to 4 The evaluation was performed in the same manner as in Example 1, except that the type and amount of polymer added were changed as shown in Table 1. For Comparative Examples 2 to 3, and Examples 2 to 3 and 5 to 11, the nail penetration test was not performed.
[0174] [Table 1]
[0175] In Table 1, "ether sulfate type ammonium salt" refers to Rearsoap "SR-10" manufactured by Adeka Corporation. "Amount added" refers to the mass ratio of the polymer (A) to the solid content of the negative electrode mixture slurry (i.e., the electrode composition).
[0176] The electrode compositions of Comparative Examples 1 to 3 did not contain the polymer (A). In Comparative Example 4, the proportion of the structural unit (a) was not more than 50 mol %. Therefore, the post-storage resistance increase rates (relative values) of Comparative Examples 1 to 4 were not less than 100. As a result, it was found that the electrode compositions of Comparative Examples 1 to 4 were not electrode compositions capable of suppressing an increase in resistance after high-temperature storage of a battery.
[0177] The electrode compositions of Examples 1 to 11 contained a polymer (A). The proportion of the polymer (A) was more than 50 mol %. Therefore, the resistance increase rate after storage (relative value) of Examples 1 to 11 was less than 100. As a result, it was found that the electrode compositions of Examples 1 to 11 are electrode compositions that can suppress an increase in resistance after high-temperature storage of a battery. [Explanation of symbols]
[0178] 1. Lithium-ion secondary battery 10 Battery element 11 Positive electrode 11A positive electrode current collector 11B Positive electrode composite layer 110 Positive electrode current collector 111 Undercoat layer 12 Negative electrode 12A negative electrode current collector 12B Negative electrode composite layer 120 Negative electrode current collector 121 Undercoat layer 13 Separator 14 Cell Layer 21 Positive lead 22 Negative lead 30 Exterior body
Claims
1. Contains a polymer (A), the polymer (A) comprises a structural unit (a) having a five- or six-membered nitrogen-containing heterocyclic structure, the nitrogen-containing heterocyclic structure being derived from a compound containing an unsaturated bond; A composition for an electrode, wherein the proportion of the structural unit (a) in the polymer (A) is more than 50 mol % relative to the total of all structural units constituting the polymer (A).
2. 2. The electrode composition according to claim 1, wherein the proportion of the structural unit (a) is 60 mol % or more.
3. The electrode composition according to claim 1 , wherein the structural unit (a) includes a structural unit derived from vinylimidazole.
4. The electrode composition according to claim 1 , further comprising an active material (B) and a binder (C).
5. The electrode composition according to claim 4 , wherein the active material (B) comprises a carbon-based compound.
6. 2. The electrode composition according to claim 1, wherein the content of the polymer (A) relative to the solid content of the electrode composition is 0.01% by mass to 1.0% by mass.
7. A current collector; A solid material of the electrode composition according to any one of claims 1 to 6, , an electrode.
8. A battery comprising the electrode according to claim 7.
Citation Information
Patent Citations
Coating liquid used for manufacturing of electrode as well as electrode and battery manufactured by using the liquid
JP2004063423A